Perspectivas del Mercado de Derivados en Colombia Retraso derivado del desconocimiento (2019)
The derivative market represents the evolution of financial markets in the world, given the capacity that the former has for offering coverage to market participants, which is an important feature in the present context of globalization. For this reason, some projects are being developed in our country, though a bit late, for the incorporation of futures and options, as new investment and financing alternatives, which may result in a reduced uncertainty for the investors in different sectors of the economy. This article shows the current situation of the derivative market in Colombia and the efforts made by different institutions, aimed at the development of such a market.